Winter according to Humphrey - Birney, Betty G. (New York : G.P. Putnam's Sons, 2012)
Humphrey the hamster and the students in Mrs. Brisbane's class get ready for the holidays and a special Winter Wonderland program.
Keywords: Schools -- Juvenile fiction; Hamsters -- Juvenile fiction; Winter -- Juvenile fiction; Holidays -- Juvenile fiction; Schools -- Fiction; Hamsters -- Fiction; Winter -- Fiction; Holidays -- Fiction; Hamsters; Holidays; Schools; Winter; Hamsters -- Fiction; Winter -- Fiction; Holidays -- Fiction; School stories; Fiction; Juvenile works; Fiction; Juvenile works; JUVENILE FICTION / Animals / Mice, Hamsters, Guinea Pigs, etc; JUVENILE FICTION / School & Education; JUVENILE FICTION / Holidays & Celebrations / General (see also Religious / Christian / Holidays & Celebrations)